Analysis of the Content of Tiktok Comments @Dictionarei in A DAY WITH REI PART 350/ SWISS DAY - Kusumarini, Cahyawati Diah; Kuncoroyakti, Yohanes Arie; Rahella, Lucky Khairulisa (Review: Journal of Multidisciplinary in Social Sciences, 2024)
This research uses a qualitative content analysis method with a constructivistic paradigm, with new media theory as its basis. The data collected for this study were 80 randomly selected relevant comments on Tiktok social media regarding their opinions on the video post "A Day With Rei Part 350/Swiss Day". The purpose of this research is to find out the content of the comments. This research found one major theme, namely Opposition to the video post 'A Day With Rei Part 350/Swiss Day'. This theme is the content of several categories that appear in the data that has been analyzed, namely Positive response, Criticism of the creator, Factual question, Personal opinion, Hope and Negative response.